Effectiveness of Digital Teaching Materials with Content Ethnoscience in Increase Digital Literacy - Mufrihah, Fadhilatul; Ellianawati, Ellianawati; Rusilowati, Ani (Unnes Science Education Journal, 2024)
This study aims to develop digital teaching materials containing ethnoscience and measure their effectiveness on junior high school students' digital literacy. School digitalization through the use of android-based learning resources is one way to improve motivation and learning achievement. This study uses the Research and Development (R&D) method with the ADDIE model. Effectiveness testing was carried out through the Paired Sample T-Test and N-gain tests. The results showed that the use of digital teaching materials containing ethnoscience was able to significantly improve students' digital literacy, with an N-gain result of 0.7 for the experimental class and an N-gain result of 0.3 for the control class showing a higher increase compared to the control class. These results support the application of digital teaching materials containing ethnoscience as an effective method in improving students' digital literacy.